Exercise enhances creativity independently of mood. Issue 3 (September 1997) - Steinberg, Hannah; Sykes, Elizabeth A; Moss, Tim; Lowery, Susan; LeBoutillier, Nick; Dewey, Alison
Abstract : Objectives: It has been widely accepted in the literature that various forms of physical exercise, even in a single session, enhance positive mood. It has also been shown that physical exercise may sometimes enhance creative thinking, but the evidence is inconclusive. Positive moods can favour creative thinking, but the opposite has also been reported and these relations are unclear. There is a large anecdotal literature suggesting that creative people sometimes use bodily movement to help overcome "blocks". The aim of this study was to establish whether post-exercise creative thinking was attributable to improved mood. Methods: The responses of 63 participants to an exercise (aerobic workout or aerobic dance) and a "neutral" video watching condition were compared. Mood was measured using an adjective list, and creative thinking was tested by three measures of the Torrance test. Results: Analysis of variance showed a large and significant increase in positive mood after exercise (P<0.001) and a significant decrease in positive mood after video watching (P<0.001). A significant increase between the creative thinking scores of the two conditions was found on the flexibility (variety of responses) measure (P<0.05). A multifactorial analysis of all data failed to show a significant covariance of creative thinking with the two measures of mood (P>0.05). Conclusions: These results suggest that mood and creativity were improved by physical exercise independently of each other.